1994
DOI: 10.1099/0022-1317-75-2-449
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular retention of hepatitis B virus surface protein mutants devoid of amino-terminal pre-S1 sequences

Abstract: To study the mechanism of L protein-mediated, intracellular (pre-Golgi) retention of hepatitis B virus (HBV) surface proteins, a collection of HBV preS-S open reading frame variants bearing wild-type or modified preS extensions was expressed in human cells. When the secretion phenotype of the corresponding proteins was analysed, all surface proteins with rearranged preS domains were found to be at least partially retained. This held true, in particular, for two variant proteins lacking preS1 amino acids 1 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…As observed in Fig 1 , functional mapping of pre-S mutations suggested that those point mutations frequently occurred in the B- and T-cell epitopes and functional domains. Point mutations in the S promoter and the CCAAT binding factors could lead to decreased synthesis of surface protein, resulting in intracellular retention of envelope proteins and ER stress, thus possibly inducing HCC carcinogenesis [ 22 24 ]. To fully explore the relationship between HBV pre-S mutations and HCC development, further elucidation of molecular mechanism focusing on hepatocyte transformation through construction of liver cell lines expressing these pre-S mutations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Fig 1 , functional mapping of pre-S mutations suggested that those point mutations frequently occurred in the B- and T-cell epitopes and functional domains. Point mutations in the S promoter and the CCAAT binding factors could lead to decreased synthesis of surface protein, resulting in intracellular retention of envelope proteins and ER stress, thus possibly inducing HCC carcinogenesis [ 22 24 ]. To fully explore the relationship between HBV pre-S mutations and HCC development, further elucidation of molecular mechanism focusing on hepatocyte transformation through construction of liver cell lines expressing these pre-S mutations are needed.…”
Section: Discussionmentioning
confidence: 99%
“…(1994). Plasmids inducing the synthesis of the proteins listed above have in part been described (Gallina et al, 1992(Gallina et al, , 1994(Gallina et al, , 1995: all D (ayw) variants; L-A and A27-I32-A (adw2). Constructs expressing ,~2-26-A, A2-80-A and A2-110-A were obtained by introducing into the A (adw2) strain preS-S gene PCR-mediated deletions, as described for the corresponding D constructs (Gallina et aL, 1995).…”
Section: And D Env Variants Expressed In 293 Cellsmentioning
confidence: 99%
“…1, top Norder et al (1994)], concluded that the L N-terminal myristic acid (Persing et al, 1987), and, independently, the N-terminal stretch 6-13, act as retention signals. On the other hand, work on D (ayw/adyw) subtypes led to a model linking retention to the specialized topogenesis of L (Prange et al, 1991;Gallina et al, 1992Gallina et al, , 1994Gallina et al, , 1995Nemeckova et al, I994). Indeed, recent reports (Ostapchuk et al, 1994;Bruss et al, 1994;Bruss & Thomssen, 1995;Prange & Streeck, 1995;Bruss & Vieluf, 1995) suggest that the L PreS domain, unlike the shorter Nterminal extensions of S and M, fails to be co-translationally translocated by downstream signals; only in a fraction of L molecules does it undergo delayed translocation into secretory cisternae (Fig.…”
mentioning
confidence: 99%
“…Overproduction of LHBs by transgenic mice containing the preS/S open reading frame (ORF) has been shown to lead to the formation of extremely long subviral particles that are prone to accumulate within the ER of the hepatocytes and not efficiently secreted (Chisari et al, 1987). This is due to the retention property of LHBs, which is partially attributed to preS1 N-terminal sequence (Gallina et al, 1994).…”
Section: Introductionmentioning
confidence: 99%